THE DEVELOPMENT OF MARINE SPATIAL PLANNING AND ITS APPLICATION FOR FLOATING FISH NET CULTURE - Dewayany Sutrisno (Department of Urban and Regional Planning, Diponegoro University, 2017)
Marine spatial planning has become the crucial issues for an archipelagic state such as Indonesia. The global market demand on marine economic species has been initiated the exploitation of the marine species which will become the hindrance in maintaining the sustainable marine biodiversity. Besides that, the degradation of marine species will also become the problem for traditional fishermen. Therefore, a model has to be employed to spatially manage the coastal waters as the alternative for fishermen activities during closed seasons, such as floating fish net culture. The aim of this study was to develop marine spatial planning model based on ecological approach in order to identify the potentiality of marine waters for marine culture such as floating fish net culture. The method for the model consisted of social assessment using the Delphi for developing the rule of marine planning for floating fish net culture and the spatial analysis technique for determining the model of marine spatial planning for floating fish net culture. The area of Kupang Bay waters, East Nusa Tenggara was used as the study area. The result indicated that the model can be used to sustainable marine spatial planning, especially for floating fish net culture. The model considered the aspects of potential area for marine culture, the management of zonation and transportation lanes, the conservation and protected area and the strategic area. Application in Kupang bay illustrated the aspect of technology input such as raceways since the majority of the area of Kupang Bay waters is classified as medium potential. Further research still needs to optimum the application of model to others marine area.